Pengaruh Konseling Kelompok Humanistik Dengan Teknik Experiential Learning Dan Client Centered Untuk Meningkatkan Kepercayaan Diri Siswa - Nanda, Septi; Japar, Muhammad; Nuraini, Paramita (Borobudur Counseling Review, 2021)
This research aims to examine the influence of humanistic group counseling with experiential learning and client centered to increase students confidence. This research is true experimental using Pretest-Post test Comparison Group Design. The subjects were chosen by random sampling. Samples taken as many as 12 students consisted of 6 students in the experimental group with experiential learning and 6 students in the experimental group with client centered. Method of data completion is done using a confident questionnaire. Data analysis for this research conducted with using Statistical Analysis One Way Anova. The results showed that humanistic group counseling with experiential learning and client centered had an influence on increasing self-confidence. This was evidenced from the results of the One Way Anova Statistical Parametric test with the probability value of sig. (2-tailed) 0.001 <0.05. Based on the analysis and discussion, there is a difference in the average score of self-confidence questionnaire between the experimental group with experiential learning by 43.38% and the experimental group with client centered by 30.22%. The results indicate that humanitstic group counseling with experiential learning have a more influence in increasing student confidance compared to humanistic group counseling with client centered.